Thermal management of metal hydride hydrogen storage tank coupled with proton exchange membrane fuel cells - Liang Tong; Chengqing Yuan; Tianqi Yang; Yupeng Yuan; Richard Chahine; Jinsheng Xiao (Case Studies in Thermal Engineering, 2023)
Metal hydride (MH), considered a promising hydrogen storage material, has received wide attention. As an efficient device for hydrogen energy utilization, a proton exchange membrane fuel cell (PEMFC) generates power and releases waste heat. MH tank can supply hydrogen for PEMFC, and the waste heat produced by PEMFC can be applied to heat the MH bed for dehydriding reaction. Thermal management between MH tank and PEMFC has been studied in this work. A lumped parameter model for the PEMFC-MH system has been developed and validated. The performance of the PEMFC-MH system has been predicted, the results show that it is feasible to use waste heat produced by PEMFC for heating the MH bed. The effect of the valve's opening degree on system performance has been investigated. The performance of the PEMFC-MH system with various output powers has been studied. The hydrogen supply rate from the MH bed to PEMFC can be adjusted based on different power requirements. The valve's opening degree can be considered an effective control measure in thermal management to improve the energy efficiency of the PEMFC-MH system.